2009
DOI: 10.1115/1.3194753
|View full text |Cite
|
Sign up to set email alerts
|

A New Laser Reflectance System Capable of Measuring Changing Cross-Sectional Area of Soft Tissues During Tensile Testing

Abstract: Determination of the biomechanical properties of soft tissues such as tendons and ligaments is dependent on the accurate measurement of their cross-sectional area (CSA). Measurement methods, which involve contact with the specimen, are problematic because soft tissues are easily deformed. Noncontact measurement methods are preferable in this regard, but may experience difficulty in dealing with the complex cross-sectional shapes and glistening surfaces seen in soft tissues. Additionally, existing CSA measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Increased strain of the Achilles free tendon measured at the same external load after exercise has been demonstrated following running (Lichtwark et al, 2013) and repeated eccentric heel drops (Obst et al, 2015), and is suggestive of early stage tendon fatigue due to mechanical creep (Fung et al, 2010). Because increased tendon longitudinal strain during tensile loading is closely associated with changes in tendon transverse morphology and strain (Obst et al, 2014b;Pokhai et al, 2009;Reeves and Cooper, 2014;Vergari et al, 2011), a similar relationship might be expected for the changes in tendon morphology and strain that occur in response to an exercise bout. In view of the high rate of exerciserelated injuries of the Achilles free tendon and the potential role short-term changes in tendon transverse dimensions could have on the local mechanical and biological environment (Heinemeier and Kjaer, 2011;Shim et al, 2014;Smith et al, 2013), there is a need to better understand the acute effects of exercise on the tendon 3D morphology and strain.…”
Section: Introductionmentioning
confidence: 71%
“…Increased strain of the Achilles free tendon measured at the same external load after exercise has been demonstrated following running (Lichtwark et al, 2013) and repeated eccentric heel drops (Obst et al, 2015), and is suggestive of early stage tendon fatigue due to mechanical creep (Fung et al, 2010). Because increased tendon longitudinal strain during tensile loading is closely associated with changes in tendon transverse morphology and strain (Obst et al, 2014b;Pokhai et al, 2009;Reeves and Cooper, 2014;Vergari et al, 2011), a similar relationship might be expected for the changes in tendon morphology and strain that occur in response to an exercise bout. In view of the high rate of exerciserelated injuries of the Achilles free tendon and the potential role short-term changes in tendon transverse dimensions could have on the local mechanical and biological environment (Heinemeier and Kjaer, 2011;Shim et al, 2014;Smith et al, 2013), there is a need to better understand the acute effects of exercise on the tendon 3D morphology and strain.…”
Section: Introductionmentioning
confidence: 71%
“…Pokhai et al (2009) reported a CSA decrease of 13.5 ± 1.9 % at 2.5 % axial strain for bovine deep and superficial digital flexor tendons. In the present study, a CSA decrease of about 10.7 ± 2.8 % was measured at tendon failure Poisson's ratio versus engineering strain for tendon #3.…”
Section: Discussionmentioning
confidence: 93%
“…Although accurate and not invasive, these systems require long acquisition times which are incompatible with dynamic or quasi-static measurements. A faster laser system (still requiring 20 s for each acquisition) was developed and applied to measure bovine tendons undergoing tensile loads (Pokhai et al, 2009); however, this system requires precise centering of the specimen in the measured zone, a task not easily performed with long specimens that can undergo tensile loads up to 20 kN. A linear scanner laser system, adapted to measurements of biological specimens CSA at rest or during mechanical testing, capable of performing fast acquisitions and not needing precise specimen centering, was recently developed (Vergari et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…The second limitation was the use of a micrometric caliper to measure the length and cross-sectional area of the grafts. Currently the laser micrometer system is the more common method to obtain the cross-sectional area of soft tissues (Moon et al, 2006a,b;Pokhai et al, 2009). However, we averaged the cross-sectional area of four levels along the tendons to eliminate any measurement errors.…”
Section: Discussionmentioning
confidence: 99%